1993
DOI: 10.1007/bf00029094
|View full text |Cite
|
Sign up to set email alerts
|

Soil redox-pH stability of arsenic species and its influence on arsenic uptake by rice

Abstract: Arsenic absorption by rice (Oryza sativa, L.) in relation to As chemical form present in soil solution was examined. Rice plants were grown in soil suspensions equilibrated under selected conditions of redox and pH, affecting arsenic solubility and speciation. A decrease in pH led to higher dissolved arsenic concentrations. When the soil redox potential dropped below 0 mV, most of the arsenic was present as As(Ill). Under more oxidizing conditions both As(Ill) and As(V) are present. Chemical speciation of As i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
140
3
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(161 citation statements)
references
References 25 publications
14
140
3
4
Order By: Relevance
“…Relatively aerobic conditions (intermittent and intermittent-aerobic treatments in the pot experiment) substantially reduced As accumulation in the shoots. Similar results have been obtained in other studies (Marin et al, 1993;Li et al, 2009b;Somenahally et al, 2011). However, Cd concentrations in straw, husk and brown rice decreased markedly in higher irrigation regimes (flooding and conventional) compared to aerobic and intermittent treatments under field conditions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Relatively aerobic conditions (intermittent and intermittent-aerobic treatments in the pot experiment) substantially reduced As accumulation in the shoots. Similar results have been obtained in other studies (Marin et al, 1993;Li et al, 2009b;Somenahally et al, 2011). However, Cd concentrations in straw, husk and brown rice decreased markedly in higher irrigation regimes (flooding and conventional) compared to aerobic and intermittent treatments under field conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Xu et al (2008) reported that during the period of active rice growth the As concentration in the soil solution was 4-13 times higher under flooded than that under aerobic conditions. It was also reported that in aerobic conditions the soil redox potential increased and arsenite was oxidized to arsenate (Marin et al, 1993). Arsenate adsorbs to the surfaces of iron oxyhydroxides and this decreases the release of As into the solution phase .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand under P starvation this cultivar had over 35% higher As concentration in shoot tissue as compared to IRGA 423 and 424 (Figure 4). Arsenite (As(III)) is the dominant As species in reducing environments such as flooded paddy soils (Marin et al 1993, Takahashi et al 2004, Xu et al 2008. Thermodynamically, reduction of arsenate to arsenite can occur quite readily at intermediate redox potentials (Inskeep et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The soil pH substantially affects the bioavailability of As and Cd and their absorption by plants (Reddy and Patrick 1977;Masscheleyn et al 1991;Marin et al 1993;Naidu et al 1994;Chan et al 2008). The soil was slightly acidic with pH 6.0 (Table 3).…”
Section: The Changes Of Ph In Soil After Si Fertilizationmentioning
confidence: 99%